Intrusión pragmática y valor epistémico - Engel, Pascal (2011)
“Pragmatic Encroachment and Epistemic Value”. Some philosopherswho defend “pragmatic encroachment” and “sensitive invariantism” argue thatchanges in the importance of being right and signiicant increases of the costsof error in given contexts can alter the standards of knowledge. If this view werecorrect, it could explain to some extent the practical value of knowledge. Thispaper argues that the pragmatic encroachment thesis is wrong. It discusses threepossible sources of encroachment on epistemic notions: on belief, on justiication,and on knowledge, and rejects the idea that the epistemic standards change withpractical stakes. Pragmatic factors can be relevant to the formation of belief andto the context of inquiry, although they are not relevant to epistemic evaluation.Epistemic value cannot depend upon such factors.